Playing God? Media coverage of CRISPR in the United States. (May 2023) - Stapleton, Patricia; Torres Yabar, Alessandra
Announcements in 2017 and 2018 that scientists used a gene editing technique called Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) to permanently alter human embryos have highlighted the urgency in regulating the technology's ethical, political, and legal implications. To better understand how a regulatory regime might evolve in response to CRISPR, we must examine how the media covers it. This article reviews online and television news sources in the United States to determine the tone, content, and frequency in media coverage of CRISPR. We find that coverage remained ambiguous and infrequent, as scientific research into CRISPR's clinical potential for treating human disease surged. This infrequent coverage indicates that the media have not yet established the salience of CRISPR to a degree that engages the public or policymakers, though the issue will continue to gain importance as CRISPR transitions from experimental efforts into clinical practice.